Expression of Amyloid Precursor Protein, Caveolin-1, Alpha-, Beta-, and Gamma-Secretases in Penumbra Cells after Photothrombotic Stroke and Evaluation of Neuroprotective Effect of Secretase and Caveolin-1 Inhibitors - Svetlana Sharifulina; Andrey Khaitin; Valeria Guzenko; Yuliya Kalyuzhnaya; Valentina Dzreyan; Alexandr Logvinov; Natalia Dobaeva; Yan Li; Lei Chen; Bin He; Svetlana Demyanenko (Biomedicines, 2022)
Our studies reveal changes in the expression of the main participants in the processing of amyloid precursor protein (APP) in neurons and astrocytes after photothrombotic stroke (PTS). Here we show the increase in the level of N- and C-terminal fragments of APP in the cytoplasm of ischemic penumbra cells at 24 h after PTS and their co-immunoprecipitation with caveolin-1. The ADAM10 α-secretase level decreased in the rat brain cortex on the first day after PTS. Levels of γ-secretase complex proteins presenilin-1 and nicastrin were increased in astrocytes, but not in neurons, in the penumbra after PTS. Inhibitory analysis showed that these changes lead to neuronal death and activation of astrocytes in the early recovery period after PTS. The caveolin-1 inhibitor daidzein shifted APP processing towards Aβ synthesis, which caused astroglial activation. γ-secretase inhibitor DAPT down-regulated glial fibrillary acidic protein (GFAP) in astrocytes, prevented mouse cerebral cortex cells from PTS-induced apoptosis, and reduced the infarction volume. Thus, new generation γ-secretase inhibitors may be considered as potential agents for the treatment of stroke.